Qualitative Study: Strengthening Teachers' Integrity Through Collaborative Academic Supervision at SDN 047/XI Koto Baru - Mailisni, Mailisni; Hadi Candra; Pristian Hadi Putra (Indonesian Journal of Counseling and Development, 2024)
This qualitative study examines the process of strengthening teacher integrity through collaborative academic supervision at SDN 047/XI Koto Baru. This research was motivated by the importance of strengthening character education as a benchmark for improving national education, with teacher integrity as one of its main pillars. The aim is to describe the process of strengthening teacher integrity through a collaborative supervision approach that is collegial, supportive, and partnership-based. The findings are expected to serve as a reference for other schools. This study used a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research informants were the principal and teachers. The collected data were analyzed through the stages of reduction, presentation, conclusion drawing, and verification. Data validity was tested using source, technique, and time triangulation techniques. The results of the study show several key findings. The actual condition of teacher integrity in this school was initially characterized by a lack of responsibility in managing learning, low discipline, and weak commitment to the school's vision and mission. After the implementation of collaborative supervision, there was an increase in teachers' motivation to innovate in learning, competence in preparing learning tools, strengthening of work ethic and responsibility, and improved discipline. The obstacles encountered included teachers' lack of ability to operate information technology, limited time to attend online workshops, and inadequate facilities and infrastructure. In conclusion, collaborative academic supervision has proven to be effective in strengthening teacher integrity, as evidenced by significant improvements in their responsibility, discipline, and professional work ethic. This approach offers a practical solution for schools seeking to foster a culture of integrity and professionalism in the workplace.